2010
DOI: 10.1021/bm100135n
|View full text |Cite
|
Sign up to set email alerts
|

AC Conductivity of Selectively Located Carbon Nanotubes in Poly(ε-caprolactone)/Polylactide Blend Nanocomposites

Abstract: DC and AC electrical conductivity of bionanocomposites based on the immiscible polymer blend poly(epsilon-caprolactone)/polylactide (PCL/PLA, w/w 70/30), loaded with multiwall carbon nanotubes (CNT), were studied in a wide frequency range, 10(-3) < or = f < or = 10(7) Hz from 143 to 313 K. The nanofiller concentration ranged from 0 to 4 wt % and it was shown to be selectively located in the PCL phase. The PCL crystallinity degree was not affected by the presence of CNT. The variation of the DC conductivity all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(99 citation statements)
references
References 44 publications
(120 reference statements)
4
93
1
Order By: Relevance
“…A schematic presentation for the arrangement of MWCNTs before percolation threshold and at percolation threshold in PC/MWCNT nanocomposites nanocomposites [23]. The current in a tunnel junction exponentially decreases with the barrier width.…”
Section: Results and Discussion 41 Electrical Analysis 411 DC Comentioning
confidence: 99%
“…A schematic presentation for the arrangement of MWCNTs before percolation threshold and at percolation threshold in PC/MWCNT nanocomposites nanocomposites [23]. The current in a tunnel junction exponentially decreases with the barrier width.…”
Section: Results and Discussion 41 Electrical Analysis 411 DC Comentioning
confidence: 99%
“…In recent times, tunneling conduction mechanism for various polymer composites has been well explained in the literature [27,28]. The tunneling conduction mechanism describes that the charge carriers move through a polymer composites across the insulating gaps between the nanofillers and generated electrical conduction in the polymer composites.…”
Section: Conductivity Measurementmentioning
confidence: 99%
“…[13][14][15][16] Besides the welldefined copolymers, the anisotropic nanofiller can also be used to improve phase morphology of an immiscible blend system in some cases. In our previous work, [17,18] the multiwalled carbon nanotubes (CNTs) were introduced into the PLA/PCL (30:70 w/w) blend as a third component. It is found that the CNTs are selectively dispersed in the continuous PCL phase and the phase interface.…”
Section: Introductionmentioning
confidence: 99%